Microbiological aspects of the effectiveness of antimicrobial drugs - Oleksandr Nazarchuk; Vasyl Nahaichuk; Viktor Paliy; Iryna Kovalenko (Kazimierz Wielki University, 2015)
Nazarchuk Oleksandr, Nahaichuk Vasyl, Paliy Viktor, Kovalenko Iryna. Microbiological aspects of the effectiveness of antimicrobial drugs. Journal of Education, Health and Sport. 2015;5(6):19-28. ISSN 2391-8306. DOI 10.5281/zenodo.18203 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A19-28 https://pbn.nauka.gov.pl/works/562794 http://dx.doi.org/10.5281/zenodo.18203 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.05.2015. Revised 28.05.2015. Accepted: 31.05.2015.   UDC: 615.28:616-001.17   MICROBIOLOGICAL ASPECTS OF THE EFFECTIVENESS OF ANTIMICROBIAL DRUGS   Nazarchuk Oleksandr1, Nahaichuk Vasyl2, Paliy Viktor2, Kovalenko Iryna1   1Department of Microbiology, Virology and Immunology, Vinnytsya National Pirogov Memorial Medical University Ministry of Health of Ukraine 2Department of General Surgery, Vinnytsya National Pirogov Memorial Medical University Ministry of Health of Ukraine   Abstract Introduction. It is well known, that patients with deep burns belong to the category of critically ill ones. According to the data of National Nosocomial Infections Surveillance (2004), Staphylococcus spp. are among leading opportunistic pathogens of infectious complications in such patients. Nowadays much attention is given to the problem of antibiotic resistance of Staphylococcus clinical strains. More often antiseptics are used in treatment of infectious complications, caused by antibiotic resistant miсroorganisms. The aim of the research was to study microbiological aspects of the effectiveness of antimicrobial drugs. Materials and methods. There were examined 372 critically ill patients with burns, having infectious complications. In all patients microbiological examinations were carried out during the first 7 days after burn trauma. There were isolated 115 clinical strains of Staphylococcus spp.. Their morphological, cultural, biochemical qualities and sensitivity to antibiotics, antiseptics were studied. Rresults of the study. We found, that clinical strains of S. aureus, S. epidermidis were highly resistant to oxacillin (46,9; 59,1 % respectively); were insensitive to clavulanate and sulbactam potentiated beta-lactams; ceftriaxone; meropenem, imipenem; ciprofloxacin. Sensitivity of Staphylococcus to amikacin, linezolid, vancomycin was found. There was shown the sensitivity of antibiotic resistant strains of Staphylococcus to decamethoxin, its polymer composition, chlorhexidine digluconate. In the research there was proved the decreasing of the effectiveness of chlorhexidine digluconate against Staphylococcus in conditions of increasing microbial load to 109 CFU/ml in 6,6 times comparably to decamethoxin drugs (p<0,001). Conclusions Resistant to the majority of antibiotics strains of Staphylococcus spp. store their high sensitivity to antiseptic decamethoxin and its polymeric composition, chlorhexidine digluconate. Microbial load increase up to 109 CFU/ml decreases antimicrobial effectiveness of chlorhexidine digluconate in 4,2 - 4,8 times.  Antibiotic resistant strains of Staphylococci do not have cross-resistance to antiseptic drugs. Clinical strains of S. aureus, S. epidermidis cause purulent-inflammatory complications in critically ill patients with burns and have resistance to oxacillin (46,9; 59,1 % respectively), beta-lactam antibiotics with clavulanic acid and sulbactam (amoxicillin/clavulanate - 67,47±9,30 %; ampicillin/sulbactam - 58,63±8,58 %;); ceftriaxone (55,75±14,24 %); carbapenems (meropenem - 64,93 - 70,35 %; imipenem - 66,43 - 66,78 %); ciprofloxacin (65,47±9,11 %). S. aureus, S. epidermidi are sensitive to amikacin (74,62 - 80,75 %), linezolid (77,2 - 87,44 %); vancomycin (91,88 - 92,46 %).   Key words: antibiotics, antiseptics, resistance, burns, comlications, microorganisms.